Studi Etnobotani Upacara Adat Budaya Menanam Padi Suku Dayak Bakati’ di Dusun Segiring Kabupaten Bengkayang - Yogi Dirgari; Syamswisna Syamswisna; Andi Besse Tenriawaru (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
The Dayak Bakati' community in Segiring Hamlet is one of the community groups that still preserve traditional ceremonies, one of which is related to the culture of planting rice. This study aims to determine the various traditional ceremonies of the Dayak Bakati Tribe related to the culture of growing rice and the types of plants used in it. The research was carried out for 2 months (July 2021 – August 2021) in Segiring Hamlet, Pisak Village, Tujuh Belas District, Bengkayang Regency. This type of research is exploratory descriptive. The results showed that in the Dayak Bakati' community in Segiring Hamlet there were several traditional ceremonies related to the culture of growing rice, including ngansa, ngawah, nyebeong pemudu', matek gerek, nyebeong naben kaja ndu naya ndu anat, and nyabakng. In carrying out traditional ceremonies, as many as 27 types of plants are used. Apart from the Dayak Bakati' tribe, several types of plants are also used by other community groups. This indicates the existence of ethnic closeness between these community groups.